2014
DOI: 10.1186/1471-2377-14-55
|View full text |Cite
|
Sign up to set email alerts
|

Observational Dutch Young Symptomatic StrokE studY (ODYSSEY): study rationale and protocol of a multicentre prospective cohort study

Abstract: BackgroundThe proportion of strokes occurring in younger adults has been rising over the past decade. Due to the far longer life expectancy in the young, stroke in this group has an even larger socio-economic impact. However, information on etiology and prognosis remains scarce.Methods/designODYSSEY is a multicentre prospective cohort study on the prognosis and risk factors of patients with a first-ever TIA, ischemic stroke or intracerebral hemorrhage aged 18 to 49 years. Our aim is to include 1500 patients. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…To what extent cognitive recovery continues beyond this time period will need further studies. In this regard, important insights are expected from the ongoing Observational Dutch Young Symptomatic Stroke Study (ODYSSEY), which aims to include 1500 patients and will be assessing cognitive function 6 weeks and 1 year after the index event . A recent study suggests that most cognitive recovery happens within the first 6 months, with little change thereafter , highlighting the importance of exploring the dynamic course of post‐stroke cognitive impairment especially early on.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent cognitive recovery continues beyond this time period will need further studies. In this regard, important insights are expected from the ongoing Observational Dutch Young Symptomatic Stroke Study (ODYSSEY), which aims to include 1500 patients and will be assessing cognitive function 6 weeks and 1 year after the index event . A recent study suggests that most cognitive recovery happens within the first 6 months, with little change thereafter , highlighting the importance of exploring the dynamic course of post‐stroke cognitive impairment especially early on.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study have been described previously. 10 For this study, we included patients with ischemic stroke. Patients were included consecutively between May 2013 until end of inclusion in February 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, some studies have shown that the prevalence of stroke is increasing among younger adults. 11-12 Investigation of the health and economic burden of stroke among those younger than 65 years is needed to guide public health interventions.…”
Section: Introductionmentioning
confidence: 99%